Convenient synthesis of polymetallic metal–organic gels for efficient methanol electro-oxidation. Issue 4 (4th February 2021) - Wang, Yan-Jiang; Wei, Jun-Hua; Li, Shuang; Luo, Jia-Yang; Chang, Xi-Wen; Sun, Ya-Ya; Pi, Qiu; Wu, Ya-Pan; Li, Dong-Sheng
Abstract : Novel Ni-based AlNiCu-MOG and AB&AlNiCu-MOG composite materials were successfully fabricated, which exhibited superior MOR activities with a current density of 17.1 and 33.24 mA cm −2, respectively. Abstract : Ni-based materials have emerged as promising anode electrocatalysts that can replace noble metals for the methanol oxidation reaction (MOR). However, the potential applications of Ni-based metal–organic gels (Ni-MOGs) in MOR have rarely been recognized. In this study, using the readily prepared Al-MOG (MIL-53(Al)) without MOR activity as a template, we fabricated AlNi-MOG and AlNi-based trimetallic MOGs (Cu, Co and Fe) by a simple solvothermal method, which could be directly used as electrocatalysts for the MOR. Among them, the as-obtained AlNiCu-MOG exhibited better MOR activity with an area-specific peak current density of 17.1 mA cm −2 than AlNi-MOG (11.46 mA cm −2 ), which could be attributed to the electron coupling between Ni and Cu. Moreover, the addition of the conductive material acetylene black (AB) could immensely increase the electric conductivity of AlNiCu-MOG, leading to its improved MOR activity with a peak current density of 33.24 mA cm −2 . These results represent an important first step towards the application of MOGs in the MOR.